Effect of Oropharyngeal Administration of Colostrum in Premature Newborns ≤32 Weeks of Gestation on the Immune Response and Neonatal Morbidity: A Double-Blind Randomized Clinical Trial - Silvia Romero-Maldonado; Diana Mercedes Soriano-Becerril; Perla Karina García-May; Enrique Reyes-Muñoz; Eudoxia Georgina Muñoz-Ortíz; Sandra Carrera-Muiños; Martha Lucía Granados-Cepeda; Jorge Arturo Cardona-Pérez; Elsa Castro-Millán; Enrique Segura-Cervantes; Guillermo Ceballos; Araceli Montoya-Estrada (Frontiers Media S.A., 2022)
IntroductionThe mother's colostrum carries immunological components, such as cytokines and immunoglobulins (Igs), derived from the maternal circulation with bacteriostatic properties.ObjectiveThe objective of this study was to evaluate the effect of oropharyngeal administration of colostrum (OPAC) vs. placebo in the first 4 days of life in premature newborns ≤32 weeks of gestation on serum Ig concentration, neonatal morbidity, and total days of hospitalization.HypothesisThe OPAC increases serum Igs and decreases morbidity and total days of hospitalization.Materials and MethodsA double-blind randomized controlled trial was carried out. Participants were randomly assigned to one of the two groups, namely, group 1: placebo (P) (n = 50) and group 2: colostrum (C) (n = 46). A blood sample was obtained at baseline and 7 and 28 days of life to quantify immunoglobulin G (IgG), immunoglobulin A (IgA), and IgM. Results: The C group showed an increase in serum IgA on day 28 expressed as median and [interquartile range]; C: 25 [12-35] vs. P: 11 [8-18], p < 0.001. There were no significant differences in neonatal morbidity. Newborns in the colostrum group showed the completed enteral feeding earlier (days), C: 13.9 ± 7 vs. P: 17.4 ± 8.4, p < 0.04; they reached the birth weight earlier, C: 10.9 ± 2.8 vs. P: 12.9 ± 4, p < 0.01, and had less days of hospitalization, C: 60.2 ± 33.8 vs. P: 77.2 ± 47.3, p < 0.04. Neonatal mortality was lower in the colostrum group than the placebo group 0% vs. 12%, respectively, without a statistical difference (p = 0.06).ConclusionIn premature newborns ≤32 weeks of gestation, the OPAC within 4 days after birth increases serum IgA concentration at day 28 compared to placebo. Similarly, OPAC decreased the days to complete enteral feeding and reach the birth weight and total days of hospitalization.Clinical Trial Registration[https://clinicaltrials.gov/ct2/show/NCT03578341], identifier: [NCT03578341].